Extracts Ethanol of Centella Asiatica Enhance Interferon-gamma and Tumor Necrosis Factor-alpha in Macrophage Culture Infected by Mycobacterium Tuberculosis - Mustika, Arifa (Federation of Asian Pharmaceutical Associations (FAPA), 2012)
Micobacterium tuberculosis has capacity to manipulate host defense pathway, particularly the ability to inhibit cellular immune response. Centella Asiatica is a medicinal plant which able to treaat inflammatory condition and infection. The aims of this research is to determine the effect of the extracts of Centella asiatica in enhancing interferon-gamma and tumor necrosis factor alpha in macrophages culture infected by Mycobacterium tuberculosis.